The Haunted mask - Stine, R.L. (London : Scholastic Children's Books, 2015)
Carly Beth's Halloween mask is so ugly, but she can't seem to get it off after she scares some of the boys in her neighborhood.
Keywords: Horror fiction; Children's stories; Masks